PELAKSANAAN PROMOSI MELALUI KEGIATAN EVENT LOMBA NON AKADEMIK TINGKAT SMP/MTS - Zulkipli Zulkipli; Ivan Riyadi; Afif Alfiyanto; Rudini Rudini; Mahin Ainun Naim (Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Luwuk, 2022)
School creativity in gathering the interest of registrants in each school is very much needed, including conducting non-academic competitions, as has been done by SMA Muhammadiyah 6 Palembang. The title of this study is